Body-part prefixes in Panoan and Takanan - Fleck, David (Pontificia Universidad Católica del Perú, 2012)
Prefijos en Matsés
Keywords: Pano--prefixacion--Amazonia; http://purl.org/pe-repo/ocde/ford#6.00.00